Post-traumatic carpal tunnel syndrome in children - Julianna Lee, BA; Eliza Buttrick, BA; Apurva S. Shah, MD, MBA (Elsevier, 2024)
Background: Given limited information about acute carpal tunnel syndrome (CTS) in children, the purpose of this study is to describe the presentation and treatment results of CTS after traumatic wrist or forearm injury in a pediatric population. Methods: In this retrospective single-center cohort study, all children with post-traumatic CTS were identified. Demographic and clinical presentation, treatment, and outcomes data were collected from the electronic medical record. Descriptive statistics were calculated for variables of interest, and Χ2 and independent sample t-tests were used for subgroup comparisons. Results: 18 patients (16 male, average age 12.8 ± 3.6 years) with post-traumatic CTS were identified. 13 presented acutely (<3 days) versus 4 subacutely (1-6 weeks) and one delayed presentation (>6 weeks) after injury. Of associated traumas, 83% (15/18) involved distal radius fractures, of which 40% (6/15) had an associated ulna fracture. The most common symptoms were numbness (78%), paresthesias (33%), and increasing pain (28%). Three patients had clinical concerns for concomitant compartment syndrome. 6 patients were initially monitored (2 acute, 3 subacute, 1 delayed). Ultimately, 16/18 underwent operative release (13/13 acute, 2/4 subacute, 1/1 delayed). At follow-up, 81% of the surgically treated patients had complete symptomatic relief. There was no statistically significant difference in treatment outcomes between acute versus subacute or delayed presentation (OR: 6.67, p = .214). Of patients with acute CTS, delayed surgery resulted in prolonged recovery (28.0 vs. 2.4 weeks, p < .001). Conclusions: Post-traumatic CTS more often presents acutely than as a delayed complication of distal radius fractures in children. The type of injury and clinical presentation can vary, but patients most often present with median neuropathy symptoms like numbness. Acute CTS should be treated urgently with carpal tunnel release. While patients with delayed presentation can trial observation, the patient will likely warrant surgery for complete symptom relief. Operative treatment for both acute and subacute cases generally results in positive outcomes. Key Concepts: (1) Post-traumatic CTS may present acutely as a complication of distal radius fractures in children with symptoms of numbness, paresthesias, and increasing pain. (2) Acute CTS should be treated with urgent carpal tunnel release to avoid prolonged recovery. (3) Children with delayed presentation of CTS can be safely monitored, but the patient often needs surgery to experience complete symptom relief. (4) Operative treatment for post-traumatic CTS in children generally results in positive outcomes. Level of Evidence: IV Case Series